2015
DOI: 10.1080/14786419.2015.1095747
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of cyclo(L-Pro-L-Tyr) and cyclo(D-Pro-L-Tyr) from Streptomyces sp. strain 22-4 against phytopathogenic bacteria

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms michiganensis. Antibacterial activity of cyclo(L-Pro-L-Tyr) and cyclo(D-Pro-L-Tyr) from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 13 publications
(11 reference statements)
1
38
0
2
Order By: Relevance
“…Cyclo(L‐Pro‐L‐Tyr) is a cyclic dipeptide (diketopiperiazine) identified in 100% of our samples and can be produced by Alternaria alternata or bacteria including Streptomyces , but we only identified A . alternata in 10.7% of our samples with culturing and 27.3% with DNA sequencing . However, we cannot exclude a possibility that this metabolite might be also produced by other members of the Pleosporales of which we identified a broad diversity using DNA sequencing .…”
Section: Discussionmentioning
confidence: 86%
“…Cyclo(L‐Pro‐L‐Tyr) is a cyclic dipeptide (diketopiperiazine) identified in 100% of our samples and can be produced by Alternaria alternata or bacteria including Streptomyces , but we only identified A . alternata in 10.7% of our samples with culturing and 27.3% with DNA sequencing . However, we cannot exclude a possibility that this metabolite might be also produced by other members of the Pleosporales of which we identified a broad diversity using DNA sequencing .…”
Section: Discussionmentioning
confidence: 86%
“…S10C). Compounds 1, 2, and 3 were found to be cinnamamide, lobophorin A, and cyclo-L-proline-L-tyrosine, respectively, by comparing 1 H (700 MHz, methanol-d 4 ) and 13 C (176 MHz, methanol-d 4 ) spectra data ( Supplementary Table S6) with data reported in the literature 13,17,37 .…”
Section: Resultsmentioning
confidence: 99%
“…Cyclo-L-proline-L-tyrosine was first reported to be produced by Streptomyces sp. strain 22-4 17 . It had activities against three economically important plant pathogens, Xanthomonas axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were cyclo(Tyr-Pro), previously reported from Aspergillus flavipes and Streptomyces sp. strains (Barrow and Sun 1994;Wattana-Amorn et al 2015), and cyclo(Phe-4-hydroxyPro), reported from Aureobasidium pullulans and unclassified marine bacteria strains (Shigemori et al 1998;Fdhila et al 2003), both diketopiperazines with varying stereochemical configurations. The compound eluting at 2.19 min with a m/z 284.1393 [M + H] + matched a single entry in Antibase, tryptophan-dehydrobutyrine diketopiperazine (Δ ppm = 0.14) (Kakinuma et al 1974).…”
Section: Chemical Analysis Of Bioactive Extractsmentioning
confidence: 99%